1976
DOI: 10.1111/j.1532-5415.1976.tb04129.x
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Study of a Case of Werner's Syndrome

Abstract: The postmortem study of a classic case of Werner's syndrome is presented. The subject was a Japanese man who died at the age of 39. Major findings included general microsplanchnia, extreme atrophy of the testes and skin, calcified aortic atherosclerosis, an increase of basophils in the pituitary, aspiration pneumonia, chronic pyelonephritis and a meningioma in the occipital area of the brain. Histologically, no osteoporosis was evident in the lumbar spine and iliac bone. The findings suggest that in Werner's s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Atherosclerosis and calcification can affect large extracranial and intracranial arteries, and small intracranial arteries [1,10,17,20]. Some patients have multiple small white matter infarcts and diffuse periventricular abnormalities in a pattern typical of small vessel disease [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis and calcification can affect large extracranial and intracranial arteries, and small intracranial arteries [1,10,17,20]. Some patients have multiple small white matter infarcts and diffuse periventricular abnormalities in a pattern typical of small vessel disease [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…In Werner's syndrome, there is a striking preponderance of neoplasms such as hepatoma, thyroid adenocarcinoma, sarcoma of uterus, carcinoma of breast and osteogenic sarcoma [4,[7][8][9]. Among the reported nervous system tumors, the most common were meningiomas [5].…”
Section: Discussionmentioning
confidence: 99%
“…Among the reported nervous system tumors, the most common were meningiomas [5]. Neural sheath sarcomas [8] and hemangiolipoma of the spinal cord [10] have also been documented. The proband in the present family had a pathologically verified meningioma in the right parietal convexity.…”
Section: Discussionmentioning
confidence: 99%
“…However, hypergonadotrophic hypogonadism, adrenal cortical hypofunction and GH deficiency was reported previously (7). In addition, some postmortem studies revealed findings of atrophy of the endocrine glands including the genital organs (8,9). The exact mechanisms which induce these clinical manifestations are still unclear.…”
Section: Discussionmentioning
confidence: 99%